Factors Affecting Customer’s Perception of Service Quality: Comparing Differences among Countries - Case study: Beauty salons in Bandung and Tokyo - Nakashima, Keiko; Putro, Utomo Sarjono; Mulyono, Nur Budi; Arai, Takeshi (School of Business and Management Institut Teknologi Bandung, 2010)
This paper examines a holistic study of analyzing several factors affecting service quality andtheir correlation with characteristic of customers based on value and life style. Furthermore,customer’s perception of service quality can be drawn from those relationships. Exploratoryfactor analysis and quantitative analysis is employed with case study of beauty salon serviceat Bandung and Tokyo. The results indicate how the quality of services is perceived differentlyby customers who have different value and life style, and also describe significant relationshipbetween value and life style with the affecting factors of service quality.Key words : service quality, value and life style, customer perception, beauty salon.